ANALISIS KIMIA 6 JENIS KAYU UNTUK HUTAN TANAMAN INDUSTRI - Gustan Pari; Nurmala Hudaya (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
This paper deals with a chemical analysis of six wood species obtained from industrial plantation Forest. The analysis comprises of the determination of holocellulose. lignin, pentosan, moisture content, ash content, silica content and solubility in cold water hot water, sodium hydroxide and ethanol benzene content. The result shows that holocellulose content ranges from 50.2 - 63.2 percent, cellulose from 42.6 - 56.2 percent. The high. celloluse content are Dipterocarpus haseltii, Diryobalanops lanceollata, Shorea and Agathis ]orantifo1ia. Lignin '(rom .24. 7 - 3'2.4 percent, pentosan from 15.2 - 19.0 percent. ash cotent from 0. 4 - 1. 8 percent. Silica content from 0.1 - a. 2 percent, moisture content from 10.2 - 32.0 percent. Solubility in cold water from 2. 0 - 5.1 percent, hot water from 3.5 - 5.8 percent, in one percent sodium hydroxide from 12.9 - 17. 6 percent and so lubility in ethano1-benzene (1:2) from 5.2 - 13.2 percent.Based on chemical analysis, especially the cellulose contants the ,six wood species for timber estate are suitable as raw material for pulp and paper industry.